Robustness of DRASTIC Method for Groundwater Vulnerability Case of Wadi Nil Aquifer in Jijel, NE Algeria - Souhil Mahdid; Nabil Chabour; Taha-Hocine Debieche; Abdelmalek Drouiche; Séverin Pistre (Indonesian Journal on Geoscience, 2022)
DOI:10.17014/ijog.9.2.229-246The alluvial water table of Wadi Nil is characterized by an abundance of groundwater, attributed to the high rainfall (1,000 mm/yr on average) of the region, the good permeability of its aquifer (10-3 to 10-4 m/s), and its significant thickness (35 to 100 m). Its waters are used for drinking water as well as for irrigation. In recent years (2000-2020), significant growth in terms of urban, agricultural, and industrial activities has developed on the plain, and has generated a significant amount of waste and effluents. In order to protect the groundwater resource, a map of the vulnerability of the water table to pollution, intended to guide public policies, has been drawn up. The DRASTIC method is a method chosen for the creation of this map, in view of its efficiency and reliability. The results obtained show that the groundwater consists of three zones: the first zone - of moderate vulnerability - is located in the outcrop areas of the marl formations (central part of the plain); the second - of high vulnerability - occupies most of the plain, composed mainly of the wadi alluvial formations; and finally the third - of very high vulnerability - is located in the downstream part of the groundwater, where the aquifer formations are sandy. The statistical analyses and sensitivity analysis of DRASTIC parameters highlight the importance of the parameters «water depth, recharge, and impact of the vadose zone» in the elaboration of the vulnerability map of the studied area, and show that the approach is relatively robust. Nevertheless, if the “water depth” and “recharge” parameters can be constrained by field measurements, the “impact of vadose zone” parameter appears to be the most delicate, because it is both sensitive and associated with uncertainties